IDENTIFIKASI POTENSI DESA GANE LUAR SEBAGAI DESA WISATA (DEWI) BAHARI DI HALMAHERA SELATAN - Halida Nuria Marus; Dewi Apriani Aco (Tekstual, 2023)
The Widi Islands, located in South Halmahera, are already famous for their white sand and several marine tourism attractions. Their location far from the hustle and bustle of the city is the reason for choosing Gane Luar Village as a Tourism Village. So it is necessary to conduct this research for the purpose of knowing the potential of the Widi Islands marine tourism village. The method used in this research is a qualitative method. In addition, there were several questions and conclusions from the answers, which the researchers submitted to several people in the Outer Gane Village as information and data materials to support this research. The results of this study are seen from the elements of tourism, namely 3A (Attractions, Accessibility, and Amenities). The first is for tourist attractions including the implementation of the Bonsole custom as a cultural attraction, fishing with fishermen from Gane Luar village, and the Kalasa mat craft. In addition, there are attractions for nature tourism, namely swimming, taking selfies, playing boats, snorkeling and diving. The second is for accessibility, namely using a ship to Bacan, using a car from Sofifi City, using a ship from Ternate to West Gane, using the Sea Toll Ship. Third, supporting amenity facilities are residents' houses as homestays, tourist huts, and health facilities: the Gane Luar Health Center.Keywords: Identification, Maritime Tourism Village, Widi Islands